Transamazônica: integrar para não entregar - NASCIMENTO, Matilde de Souza (Universidade Federal do Pará, 2020)
This article discusses how the dictatorial government of General Emilio Garrastazu Médici used symbolic elements as the basis for the legitimation of the occupation of the Amazon. The objective is to discuss, based on the concepts of nation, civilization, and conquest, how the occupation and development efforts of the region mobilized material and ideational energies to promote the occupation of the Amazon. This process took place within the scope of the National Integration Program, in which the construction of the Transamazon Highway was of great importance. Using bibliographic, documentary, and material sources disseminated by some vehicles of the great Brazilian press at the time, the article shows the mystique of national integration elaborated from some symbolic elements such as the Eldorado, the paradise, the hell, the green desert, the solitude. The methodology used was document and discourse analysis. The conclusion is that the National Integration Plan did not reduce the drought problem in the northeastern backlands, nor did it complete national integration. The latter remained as a purpose, along with the ongoing settlement projects and occupation initiatives.